2010
DOI: 10.1007/7854_2010_80
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender and Puberty on the Heritability of Disordered Eating Symptoms

Abstract: Eating disorders and disordered eating symptoms are clearly heritable, but recent research has suggested that genetic and environmental influences on disordered eating symptoms vary as a function of gender and development. Data are limited, but evidence suggests that gender may moderate the type of genetic risk, rather than the magnitude of genetic effects, on disordered eating symptoms. Only a moderate proportion of the genetic influences on disordered eating symptoms are shared between males and females. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Although there are nominal genetic effects for disordered eating in pre-pubertal twins, there are significant genetic effects for female pubertal and young adult twins (Culbert, Burt, McGue, Iacono, & Klump, 2009). In females, ovarian hormones, particularly estradiol, and the consequent increase in body fat and weight during the pubertal transition trigger heightened weight and shape concerns and disordered eating behaviors (Culbert, Racine, & Klump, 2011). The contribution of ovarian hormones could also explain the consistently reported high ratio of females to males for eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are nominal genetic effects for disordered eating in pre-pubertal twins, there are significant genetic effects for female pubertal and young adult twins (Culbert, Burt, McGue, Iacono, & Klump, 2009). In females, ovarian hormones, particularly estradiol, and the consequent increase in body fat and weight during the pubertal transition trigger heightened weight and shape concerns and disordered eating behaviors (Culbert, Racine, & Klump, 2011). The contribution of ovarian hormones could also explain the consistently reported high ratio of females to males for eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior genetic data have consistently indicated that both genetic and environmental influences contribute to eating disorders and disordered eating symptoms. Across different populations and measurement methods, twin and adoption studies have found moderate‐to‐high heritability of AN, BN, and BED ( h 2 estimates: median ~52%, mean ~50%, range ~28–88%) and disordered eating symptoms ( h 2 estimates: median ~50%, mean ~49%, range ~20–85%) in females and males during adolescence and adulthood (for reviews, see Culbert, Racine, & Klump, ; Trace, Baker, Peñas‐Lledó, & Bulik, ). Nonshared environmental effects (i.e., environmental effects that serve to create behavioral differences between siblings) generally account for the remaining variance.…”
Section: Behavioral Genetic Models: Broad Evidence For Genetic and Enmentioning
confidence: 99%
“…Part of the genetic variation is also shared by anorexia nervosa and bulimia nervosa, suggesting that they partly share the same neurobiological background (Thornton et al, 2011). Previous twin studies have been underpowered to detect sex differences in the heritability of eating disorders, but there is some suggestive evidence that somewhat different sets of genes affect eating disorders in males and females (Culbert et al, 2011). GWA studies have been conducted for anorexia nervosa, whereas little is known on the candidate genes of bulimia nervosa and binge eating disorder (Himmerich et al, 2019).…”
Section: Genetics Of Eating Behaviormentioning
confidence: 99%